2014
DOI: 10.1177/0193945914525280
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Burden, Health Status, and Learned Resourcefulness of Older Caregivers

Abstract: As caregivers undertake caregiving responsibilities over a long period of time, the burdens placed on them could lead to undue stress and affect their health. This correlation study examined the current situations and relationships among caregiver burden, health status, and learned resourcefulness (LR) of older caregivers who care for disabled older adults, and predicted the important factors that affect their caregiver burden. In all, 108 older caregivers were recruited from home care services of two hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 23 publications
2
29
0
3
Order By: Relevance
“…Because of the high costs associated with PD‐related care, the increasing incidence and prevalence of PD and the aging population of the United States overall, it is important to understand the economic burden on PD caregivers . In addition, direct costs may be even higher among elderly caretakers given their own predisposition to higher need for health care and higher physical strain that could be imposed . However, older caregivers are more likely to be retired or unemployed, thus the results of this study regarding the indirect costs of PD caregiving are not likely to generalize to elderly caregivers .…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Because of the high costs associated with PD‐related care, the increasing incidence and prevalence of PD and the aging population of the United States overall, it is important to understand the economic burden on PD caregivers . In addition, direct costs may be even higher among elderly caretakers given their own predisposition to higher need for health care and higher physical strain that could be imposed . However, older caregivers are more likely to be retired or unemployed, thus the results of this study regarding the indirect costs of PD caregiving are not likely to generalize to elderly caregivers .…”
Section: Discussionmentioning
confidence: 84%
“…34 In addition, direct costs may be even higher among elderly caretakers given their own predisposition to higher need for health care and higher physical strain that could be imposed. 35 However, older caregivers are more likely to be retired or unemployed, thus the results of this study regarding the indirect costs of PD caregiving are not likely to generalize to elderly caregivers. 36 The high prevalence of PD in the United States further underscores the magnitude of the burden of this disease.…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, the inverse relationships between resourcefulness and depressive symptoms and stress among these caregivers suggest that low resourcefulness poses a risk to the psychological wellbeing of women dementia caregivers. Previous studies have also shown high risk of depression and stress among individuals with low resourcefulness, which are indicators of high need for resourcefulness training (Chen, Chen, & Chu, 2014; Peterson, 2013; Zauszniewski, Bekhet, & Suresky, 2009; Zauszniewski, et al, 2012; Bekhet, Zauszniewski, & Matel-Anderson, 2012). …”
Section: Discussionmentioning
confidence: 98%
“…For instance, if caregiving tasks are appraised as non‐stressful and meaning giving, levels of depression were low and life satisfaction high (Haley, LaMonde, Han, Burton, & Schonwetter, ; Li et al., ). However, compared to non‐caregivers, family carers looking after frail older persons exhibit higher burden and depression (Chen, Chen, & Chu, ; Pinquart & Sorensen, ). The intensity and duration of caregiving have also been associated with more negative outcomes, such as psychological well‐being and depression (Marcia Grant et al., ; Pinquart & Sorensen, ).…”
Section: Discussionmentioning
confidence: 99%